2010
DOI: 10.1007/s11199-010-9788-0
|View full text |Cite
|
Sign up to set email alerts
|

Racism and Sexism as Correlates of African American Women’s Psychological Distress

Abstract: Historically, researchers have neglected the lives of African American women, and very little research has looked specifically at concurrent examinations of multiple oppressions associated with multiple minority identities as predictors of mental health. The current study aimed to increase our knowledge about African American women by examining the relations between external and internalized racism and sexism and African American women's psychological distress. One hundred sixty participants were recruited thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
105
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 52 publications
(69 reference statements)
14
105
2
Order By: Relevance
“…For example, when facing prejudice experiences, women of color likely consider the potential roles that racism and sexism are playing during the event. Recent studies have explored the gendered racism that African American women experience and the impact on their psychological distress, noting the difficulty in trying to separate their experiences of racism from experiences of sexism (Szymanski and Stewart 2010;Thomas et al 2008). Future research should continue to explore experiences of gender prejudice in the lives of women from various age groups, ethnic populations and socioeconomic status.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, when facing prejudice experiences, women of color likely consider the potential roles that racism and sexism are playing during the event. Recent studies have explored the gendered racism that African American women experience and the impact on their psychological distress, noting the difficulty in trying to separate their experiences of racism from experiences of sexism (Szymanski and Stewart 2010;Thomas et al 2008). Future research should continue to explore experiences of gender prejudice in the lives of women from various age groups, ethnic populations and socioeconomic status.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies have suggested that the intersection between race and class have important implications for African American females' social experiences and subsequent mental health outcomes (e.g., Keith and Brown 2010;Szymanski and Stewart 2010). In particular, research has indicated that African American females from lower socioeconomic backgrounds may be at an increased likelihood for stress exposure (e.g., Siefert et al 2007).…”
Section: Socio-economic Backgroundmentioning
confidence: 99%
“…M embers of cultural minority groups tend to experience disproportionate amounts of psychological distress and disorders in comparison to the general population Szymanski & Stewart, 2010;U.S. Surgeon General, 2001).…”
mentioning
confidence: 99%